2008
DOI: 10.1007/s00417-008-0791-x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in retinal thickness are correlated with alterations of electroretinogram in eyes with central retinal artery occlusion

Abstract: Measurement of retinal thickness by OCT can be useful for monitoring the changes following CRAO. The correlation between the retinal thickness, especially inner layer thickness, and the ERG components was determined, suggesting that the PhNR in the acute phase might be a good indicator for predicting the thinning of the damaged retina in the chronic phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 10 publications
3
30
0
1
Order By: Relevance
“…Evaluation of the extracranial carotid system can be performed by ultrasonography, magnetic resonance angiography (MRA), or computed tomography angiography (CTA) [10]. An ECG can identify an underlying cardiac arrhythmia.…”
Section: Diagnostic Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Evaluation of the extracranial carotid system can be performed by ultrasonography, magnetic resonance angiography (MRA), or computed tomography angiography (CTA) [10]. An ECG can identify an underlying cardiac arrhythmia.…”
Section: Diagnostic Evaluationmentioning
confidence: 99%
“…Intravenous fluorescein angiography (IVFA) and optical coherence tomography (OCT) can be useful as confirmatory tests in the setting of an uncertain diagnosis [2, 9,10]. IVFA characteristically shows delayed or restricted retinal arteriole filling [24], whereas OCT displays increased inner retinal layer thickness in the acute phase [10].…”
Section: Diagnostic Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Optical coherence tomography may demonstrate an increased inner retinal layer thickness in the acute phase due to the retinal oedema and optic nerve swelling. 40 Assessment of vascular risk Physical examination should be undertaken with a focus on the cardiovascular system to determine potential causes. The radial pulse rate and rhythm are important, as irregularly irregular rhythms suggest atrial fibrillation, which is a risk for embolic phenomena.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…10 Another study demonstrated that decreased inner layer thickness was correlated to the chronicity of CRAO, and the ratio of inner layer thickness to neurosensory retinal thickness correlated to ERG changes in patients with CRAO. 8 Macular thickness profiles have also been evaluated as aids in prognosticating ultimate visual outcomes in CRAO in one study. Mean foveal thickness in CRAO patients was 299 AE 76 microns, and mean total macular volume was 7.90 AE 0.93 mm 3 at initial examination, and declined to 167 AE 30 microns and 4.85 AE 0.68 mm 3 .…”
Section: Functional Outcomesmentioning
confidence: 99%